STRATEGI PEMBELAJARAN HADIS PADA ANAK USIA DINI DI RA NURUTTAQWA BANJARMASIN - Alfiana Falan Syarri Auliya; Anggita Gunati Fashlah; Laila Mubarakah (LP2M IAIN Sultan Amai Gorontalo, 2025)
Early childhood is a golden age that plays a crucial role in laying the foundation of education, particularly in developing moral and religious values through the learning of hadith. Hadith learning at RA Nuruttaqwa Banjarmasin is implemented as part of character building and the habituation of Islamic behavior among children. This study aims to describe the planning, implementation, and assessment of hadith learning for early childhood at RA Nuruttaqwa Banjarmasin. The research employed a qualitative approach with data collected through observation, interviews, and documentation involving the head of the institution and group teachers. The findings reveal that hadith learning is planned at the beginning of each semester by setting objectives, processes, and target hadiths to be achieved. Implementation is carried out using habituation, movement, and demonstration methods tailored to the content of each hadith, with a target of one hadith per month. Assessment is conducted daily and semesterly through observation, checklists, and rewards such as praise for children who have memorized the hadith. In conclusion, the hadith learning strategy at RA Nuruttaqwa significantly contributes to shaping Islamic character and behavior in early childhood. It is recommended that teachers continue to develop more interactive learning methods and media and conduct periodic evaluations to ensure that hadith learning emphasizes not only memorization but also comprehension and the application of hadith values in daily life. Keywords: learning strategy, hadith learning, early childhood